Uji Daya Antelmetika Ekstrak n-Heksan Rimpang Bangle (Zingiber cassumunar) pada Cacing Ascaris suum secara In Vitro - Soleha, Maratu; Purba, Anny Victor (Jurnal Kefarmasian Indonesia, 2013)
The objective of this research was to investigate the anthelmentics activities of Zingiber cassumunar rhizome n-hexane extract against Ascaris suum in-vitro. The experiments were carried out by using immersion method. The worm were soaked in extract of Zingiber cassumunar rhizome . One hundred and forty four ascaris worms were divided into 8 groups; each Petri contain 6 wors of Ascaris suum the dosage in every Petridish was 1 x LD50 (15,78 mg/100 ml), 2 x LD50 (31,56 mg/100 ml), 4 x LD50 (63,12 mg/100 ml), 8 x LD50 (126,24 mg/100 ml) and 12 x LD50 (189,36 mg/100 ml). The positive control used was pirantel pamoat 250 mg/100 ml and as negative controls were solutions like intestine and carboxy methyl cellulose 0,94% suspension. Experiment result shows that dosage 5 (189,36 mg/100 ml) was the most optimum dosage for anthelmentics treatment in that dosage 27,8% Ascaris suum were dead. Anthelmentics investigation was done by counting the deaths of Ascaris suum which were emmersed for 24 hours. The infusion of zingiber cassumunar has strongest activity as anthelmentics rather than in alcohol and n-hexane extract forms.